FEATURES OF THE ORGANIZATION AND MANAGEMENT OF AWARDS IN UKRAINE DURING THE WAR AND POST-WAR PERIODS - ANDRUSHKIV, Bohdan; CHEREP, Olexandr; KYRYCH, Nataliia; POHAJDAK, Olha; BOIKO, Ostap (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines the peculiarities of the development of the award case in the conditions of the war and in the post-war period. It has been studied that in the conditions of war, one of the important levers for raising the efficiency of the organization as production, social coexistence, defense work, social development is the reward factor and tools, which are formed on the basis of the state ideological doctrine, the political situation, the state of socio-economic development, and the personnel policy of the state in the sectoral and territorial spheres and the scientific validity of management decisions in this specific area. The reward policy as a component of the formation of the management strategy for the future, in the post-war period in the context of Ukraine's accession to the EU and NATO, is a derivative of the implemented general strategy of the state's development. As a rule, the direct object of the award case in the state administration is not only the personnel potential of state authorities, industry and territorial sectors of the national economy, but also, of course, the personnel of the civil service, local self-government bodies, and society.Actually, these circumstances determined the expediency of the formation of organizational and economic mechanisms for the management of award activities, and with their use it is necessary to coordinate and establish relationships (the work of the public sector of Ukraine, we mean the award department of the President's office), executive bodies of the state and local self-government bodies, territorial communities and public organizations in war and post-war (for the future) circumstances, both in the industry and in the territorial sectors of the National Economy. The article attempts to determine the reasons for the ineffectiveness of reward policy, at the current stage, and proposes an updated system of reward principles and ways to solve this problem in the war and post-war period in the context of our country's accession to NATO and the EU.The development of a scientifically based, clear and transparent reward management system is an urgent need of Ukrainian society, the most important prerequisite for strengthening the state, strengthening its defense positions, restoring the national economy and preparing for joining the EU and NATO.
Keywords: award case; organization; management; EU; NATO; ideology; politics; strategy; war; post-war period; material and moral interest; industries; territory; state